Como idéias se transformam em reformas: um estudo comparativo das mudanças educacionais orientadas pelo desempenho nos estados brasileiros - Segatto, Catarina Ianni (2011)
The research focuses on the discussion public policy design, namely the process through which similar performance oriented ideas turned in different reforms. These performance oriented ideas were present in numerous reforms recently disseminated in the Brazilian states, mainly in Education. The need to improve government performance, to do the retrenchment policy and the low accountability were the main impetus for the implementation of reforms in the Brazilian states. In Education, the adoption of the reforms was due to the low performance of students in international and national ratings and, moreover, its dissemination was influenced by a number of actors and institutions, international organizations, Federal Government, federative forums and civil society organizations. Despite the dissemination of this type of reform in Education, each reform has a specific design. In order to understand which variables influence the reforms design, we have reviewed and systematized the literature on public policy and political science that seeks to explain this problem and we conducted questionnaires and qualitative interviews with those who were responsible for reforms in selected states as well as the analysts of education policy. The conclusion is that the political trajectory is a key element to understand this process.